Parametric Audio Based Decoder and Music Synthesizer for Mobile Applications - SZCZERBA, Marek; OOMEN, Werner; THERSSEN, Dieter (Archives of Acoustics, 2011)
This paper reviews parametric audio coders and discusses novel technologies introduced in a low-complexity, low-power consumption audio decoder and music synthesizer platform developed by the authors. The decoder uses parametric coding scheme based on the MPEG-4 Parametric Audio standard. In order to keep the complexity low, most of the processing is performed in the parametric domain. This parametric processing includes pitch and tempo shifting, volume adjustment, selection of psychoacoustically relevant components for synthesis and stereo image creation. The decoder allows for good quality 44.1 kHz stereo audio streaming at 24 kbps. The synthesizer matches the audio quality of industry-standard samplebased synthesizers while using a twenty times smaller memory footprint soundbank. The presented decoder/synthesizer is designed for low-power mobile platforms and supports music streaming, ringtone synthesis, gaming and remixing applications.